PENGARUH PELAYANAN BERBASIS DIGITAL TERHADAP KEGIATAN AKADEMIK DI UNIVERSITAS MUHAMMADIYAH GORONTALO - Panigoro, Muslim; Akbar, Muh. Firyal; Pakudu, Robin (Gapenas Publisher, 2025)
This study examines the effect of digital-based services on academic activities at Universitas Muhammadiyah Gorontalo. The rapid development of digital technology in the era of the Industrial Revolution 4.0 has significantly influenced public services, including higher education institutions. This research employs a quantitative associative approach with a sample of 98 students selected from a population of 3,800 using the Slovin formula. Data were collected through questionnaires and analyzed using validity and reliability tests, correlation analysis, and simple linear regression. The findings reveal that digital-based services have a positive but weak and statistically insignificant relationship with academic activities, as indicated by a regression coefficient of 0.382 and a significance value of 0.052. The weak influence is primarily due to limited student digital literacy, dependence on electricity infrastructure, and unstable internet access. These challenges hinder the optimization of digital services in supporting academic processes. The study suggests the need for continuous digital literacy training, improved infrastructure, reliable internet access, and collaboration with service providers to enhance the effectiveness of digital-based academic services.